2011
DOI: 10.1155/2011/269519
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recovery after Cyclophosphamide Treatment in Multiple Myeloma: Implication for Maintenance Immunotherapy

Abstract: Multiple myeloma (MM) is a progressive B-lineage neoplasia characterized by clonal proliferation of malignant plasma cells. Increased numbers of regulatory T cells (Tregs) were determined in mouse models and in patients with MM, which correlated with disease burden. Thus, it became rational to target Tregs for treating MM. The effects of common chemotherapeutic drugs on Tregs are reviewed with a focus on cyclophosphamide (CYC). Studies indicated that selective depletion of Tregs may be accomplished following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
0
14
0
1
Order By: Relevance
“…Despite the lack of evidence in regard to cyclophosphamide's effect on Tregs in systemic autoimmune diseases, contradictory results were reported from studies in cancer. In this case, cyclophosphamide exerts a more complicated effect on immune cells than previously considered . Beside its tumoricidal effect in high doses, this agent demonstrated a potent immunosuppressive function via lymphocyte ablation.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the lack of evidence in regard to cyclophosphamide's effect on Tregs in systemic autoimmune diseases, contradictory results were reported from studies in cancer. In this case, cyclophosphamide exerts a more complicated effect on immune cells than previously considered . Beside its tumoricidal effect in high doses, this agent demonstrated a potent immunosuppressive function via lymphocyte ablation.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies show that low doses of cyclophosphamide are highly toxic to Treg cells 20. In contrast, Condomines in a study of 14 patients mobilized with high dose cyclophosphamide found a 2-fold increase in Treg cells, speculating that a cytokine burst following aplasia due to cyclophosphamide is responsible 11.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of cyclophosphamide on Treg cells depends on the dose of cyclophosphamide and the addition of G-CSF. Low doses of cyclophosphamide have a specific toxicity to Treg cells, thereby decreasing their numbers and potentially increasing an immune response against myeloma cells 20. On the opposite, high doses of cyclophosphamide in combination with G-CSF increase the number of Treg cells by 2-3 fold 11.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel also reduced the number of regulatory T (Treg) cells and myeloid-derived suppressor cells (MDSCs), and led to the augmentation of the functions of CD4 and CD8 T cells (16,17). In other cases, DNA alkylating agents, such as cyclophosphamide and mafosfamide, in low doses selectively depleted Treg cells (18,19), caused an increase in effector T cells (Teff)/Treg cell ratios via up-regulation of the T helper (Th) 17 pathway (20), and improved the outcome of tumor vaccinations against cancer (21)(22)(23). Furthermore, doxorubicin, mitomycin C, vinblastine, and methotrexate in low doses have been found to up-regulate DC maturation, antigen processing, and antigen presentation, which led to synergistic antitumor effects of low-dose chemotherapy combined with a DC vaccine (24)(25)(26).…”
Section: Significancementioning
confidence: 99%